ENHANCING YOUNG LEARNERS' SPEAKING SKILLS WITH DIFFERENT METHODS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The acquisition of speaking skills is crucial in the language development of young learners. This paper explores the efficacy of diverse pedagogical approaches in enhancing the speaking proficiency of young language learners. Drawing from contemporary educational theories and empirical research, the study investigates the impact of communicative language teaching, task-based learning, storytelling, and technology integration on young learners' speaking abilities. The study employs a mixed-methods approach, incorporating both qualitative and quantitative measures to evaluate the effectiveness of each pedagogical method. Qualitative data is gathered through classroom observations and student interviews to assess engagement, motivation, and learner perceptions. Quantitative data is collected through pre- and post-assessment speaking tests to measure improvements in speaking fluency, accuracy, and complexity. Preliminary findings suggest that a combination of communicative language teaching and task-based learning fosters authentic communication and meaningful interaction among young learners. Additionally, integrating storytelling activities provides a creative outlet for language expression and enhances speaking confidence. Furthermore, leveraging technology, such as interactive multimedia tools and online platforms, offers opportunities for authentic language practice and facilitates self-directed learning. This paper contributes to the existing literature by providing empirical evidence of effective pedagogical strategies for promoting speaking skills in young language learners. The findings underscore the importance of employing diverse and dynamic approaches to cater to the diverse needs and learning styles of young learners, ultimately fostering their proficiency and confidence in spoken language communication.